La promoción de la salud en el ámbito escolar del Colegio José Celestino Mutis - María Victoria Díaz-G; Gonzalo Jaramillo-D (Universidad de Antioquia, 2005)
The school population can be impacted on their quality of life, when considering health topics as part of the curriculum or in an extracurricular way when health problems, the culture and the strengths of the context are considered. With the purpose of implementing the educational strategy for health in the José Celestino Mutis School in the city of Medellín, a thematic participated study was undertaken, it arose from the acknowledgement of the local context, the socio-economical, epidemiological and cultural conditions of the school's population; also the knowledge and health practices promoted there; the health thematic units that would make part of the Institutional Educational Project were identified. The knowledge and health practices were recognized in mothers, teachers and students placing special importance on the child and its environment. The home is confirmed as the primary place of socialisation, where mothers consider health as an instrument that allows the best development of the child. In the same manner, the school as the second place of socialization, mothers place their expectations in the comprehensive development of their children which is perceived by teachers as a delegated responsibility from parents. In order for health education to be operative, Centers of Interest were found to be a good instrument with which Health Thematic Units would be developed, parting from the construction of knowledge that presents significant learning situations for the child according to his/her level of development.